A multi-institutional randomized phase III trial comparing anatomical segmentectomy and wedge resection for clinical stage IA non-small cell lung cancer in high-risk operable patients: Japan Clinical Oncology Group Study JCOG1909 (ANSWER study). (20th July 2020) - Shimoyama, Ryo; Tsutani, Yasuhiro; Wakabayashi, Masashi; Katayama, Hiroshi; Fukuda, Haruhiko; Suzuki, Kenji; Watanabe, Shun-ichi; ,
Abstract: Anatomical segmentectomy or wedge resection is recommended for high-risk operable patients with clinical stage IA non-small cell lung cancer in guidelines of the National Comprehensive Cancer Network and the Japanese Lung Cancer Society. However, there is no clear evidence comparing the sublobar resections. The less invasive and more generally performed is wedge resection but anatomical segmentectomy may have better survival benefits than wedge resection owing to its superiority in locoregional control. In April 2020, we have initiated a randomized phase III trial in Japan to confirm the superiority of anatomical segmentectomy over wedge resection in high-risk operable patients with clinical stage IA non-small cell lung cancer. We plan to enroll a total of 370 patients from 47 institutions over a period of 5 years. The primary endpoint is overall survival; the secondary endpoints are adverse events, postoperative respiratory function, relapse-free survival, proportion of local recurrence, operative time and blood loss. Abstract : This trial aimed to confirm the superiority of anatomical segmentectomy over wedge resection in terms of overall survival in high-risk operable patients with clinical stage IA non-small cell lung cancer.